GC-MS Analysis of Bioactive Compounds in Ethanol and Ethyl Acetate Fraction of Grapefruit (Citrus maxima L.) Rind - La Ode Muhammad Andi Zulbayu; Endang Lukitaningsih; Rumiyati Rumiyati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The grapefruit (Citrus maxima L.) is a plant known by the public as a fruit consumed with various properties. This plant's use is well known, such as antioxidants, enhancing immunity, anti-aging, and antibacterial properties. This study aimed to identify and analyze the chemical compounds contained in C. maxima rind. The extract was obtained by the maceration method using ethanol and ethyl acetate as solvents. The fractionation process was carried out by Column Chromatography. Observation of thin-layer chromatography profiles with UV lamps 254 and 366 nm. Analysis of chemical compound components using GC-MS and data interpretation based on the Wiley 7.0 data library. The interpretation results of the EF1 fraction were β-copaen-4-α-ol, pentadecanoic acid, hexadecanoic acid, tetradecanoic acid, dotriacontane, osthol, 2H-1-benzopyran-2-one, 7-methoxy-8-(3-methyl-2-oxobutyl), furfural, 6-(2,3-Dihydroxy-3-methylbutyl)-7-methoxycoumarin, and 6-(iodomethyl)-5-methyl-4-oxahexanolide. The chemical compounds identified in EAF2 were 1-octadecanol, decane, tetracosane, hexacosane, and 1,2-benzenedicarboxylic acid (2-ethylhexyl) ester. It can be concluded that these compounds have biological and pharmacological activities.